2016
DOI: 10.1073/pnas.1606800113
|View full text |Cite
|
Sign up to set email alerts
|

Men’s status and reproductive success in 33 nonindustrial societies: Effects of subsistence, marriage system, and reproductive strategy

Abstract: Social status motivates much of human behavior. However, status may have been a relatively weak target of selection for much of human evolution if ancestral foragers tended to be more egalitarian. We test the "egalitarianism hypothesis" that status has a significantly smaller effect on reproductive success (RS) in foragers compared with nonforagers. We also test between alternative male reproductive strategies, in particular whether reproductive benefits of status are due to lower offspring mortality (parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
150
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(161 citation statements)
references
References 83 publications
8
150
0
3
Order By: Relevance
“…, it does match the generalization that many authors have made, as reviewed in the von Rueden and Jaeggi article (4), that our species exhibits much less reproductive skew than our primate relatives, and supports the common inference that hypersociality in our lineage has transformed (but not eliminated) the dominance system characteristic of higher primates. von Rueden and Jaeggi (4) conclude that because huntergatherers do not differ from societies with other subsistence modes in degree of status-RS association, "positive selection for traits that facilitate status acquisition (including men's motivation to seek it) did not increase substantially when foragers began domesticating plants and animals" (4).…”
Section: The Egalitarian Hypothesissupporting
confidence: 86%
“…, it does match the generalization that many authors have made, as reviewed in the von Rueden and Jaeggi article (4), that our species exhibits much less reproductive skew than our primate relatives, and supports the common inference that hypersociality in our lineage has transformed (but not eliminated) the dominance system characteristic of higher primates. von Rueden and Jaeggi (4) conclude that because huntergatherers do not differ from societies with other subsistence modes in degree of status-RS association, "positive selection for traits that facilitate status acquisition (including men's motivation to seek it) did not increase substantially when foragers began domesticating plants and animals" (4).…”
Section: The Egalitarian Hypothesissupporting
confidence: 86%
“…In this model, elevated OT during socially salient conditions serves to activate mentalizing networks to enhance social cognition, which can lead to social reward (e.g., in bonded relationships) or heightened anxiety (e.g., in unresolved interpersonal conflict). It is well characterized that in small-scale societies men who are very successful at securing resources often earn social status in their communities (von Rueden & Jaeggi, 2016); thus, given the social reward of acquired status (von Rueden & Jaeggi, 2016), such fathers could plausibly have elevated OT, based on some psychobiological frameworks (Bartz et al, 2011;Bethlehem et al, 2014;Crespi, 2016).…”
Section: Méthodeismentioning
confidence: 99%
“…In this work, signaling theory has largely been used to explain three broad types of behavior: (a) the pursuit of risky resources, especially when the resources are widely shared (Box B); (b) contribution to a public good, as with blood donation (Box C); and (c) religious behaviors that entail sizable investments of time, money, and energy in the name of the divine (Box A). Empirical investigations have suggested that signals result in improved status and reputational standing, leading to increased social support and well‐being, and ultimately reproductive success …”
Section: Introductionmentioning
confidence: 99%
“…Empirical investigations have suggested that signals result in improved status and reputational standing, 25 leading to increased social support and wellbeing, 11,14,19,21,22,27 and ultimately reproductive success. [29][30][31] Behavioral ecologists have continued to develop and refine signaling theory since its introduction to anthropology in the late 1990s.…”
mentioning
confidence: 99%